Information technology for management : improving quality and productivity - Turban, Efraim; McLean, Ephraim; Wetherbe, James (New York : John Wiley, 1996)
Business
2002-05-22
Keywords: Information techonology; Information systems; Information systems technology; Information systems development; Information systems analysis and design; Information support systems; Managing inforamtion technology